The Effectiveness Of Augmented Reality Learning Media Integrating Toraja Carving Ethnomathematics On Students’ Mathematical Proficiency - Yuda Satria Nugraha; Vaira Indah Wahyuni; Nurwahida (Koordinat Jurnal MIPA, 2026)
This study aims to investigate the effectiveness of Augmented Reality (AR) learning media integrating Toraja carving ethnomathematics on the mathematical proficiency of ninth-grade junior high school students in Palopo. The research employed a quasi-experimental design using a pre-test and post-test model to measure the impact of AR learning media on students’ mathematical skills. The participants consisted of 150 students selected from six schools through purposive and random sampling techniques. The research instruments comprised a mathematical proficiency test and a questionnaire developed based on five indicators: conceptual understanding, procedural fluency, strategic competence, adaptive reasoning, and productive disposition. Data were analyzed using the Wilcoxon Signed-Rank Test, as the dataset was not normally distributed. The results indicate a significant improvement in students’ mathematical proficiency after the implementation of AR learning media, as evidenced by the significance value of the Wilcoxon Signed-Rank Test, which is 0.000 and lower than 0.05. The integration of AR technology with local cultural elements of Toraja carvings successfully fostered a contextual, interactive, and meaningful learning environment. This study implies that can serve as an innovative pedagogical approach to enhance mathematical proficiency while promoting the preservation and appreciation of local culture in mathematics education